TA'LIM AL-LUGHAH 'ABR AL-TSAQAFAT WA TATHBIQUHU FI TA'LIM AL-LUGHAH AL-'ARABIYAH FI INDONESIA - Nasaruddin, Nasaruddin (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2015)
This article examines the close relationship that exists between language and culture which  reflected in that language is a pot of culture and culture is a frame of language usage. It follows from this relationship that language learning is the linguistic and cultural process, or what so-called teaching language across cultures. This cultural teaching of language is based on three theories first of which is “Contrastive Analysis”, “Learning The Language Is A Cultural Learning”, and “Cultural Awareness In Foreign Language Teaching And Learning”. Based on these three theories this article tries to put down a cultural pattern for the teaching of Arabic for Indonesian learners which has cultural goals and content.  It aims at overcoming linguistic and cultural problems suffered by the Indonesians when learning the Arabic, especially their difficulty in understanding Arabic elements that are different from what in their language, and their difficulty  in using Arabic in certain situations properly.DOI: 10.15408/a.v2i2.2141